Mo2C quantum dot embedded chitosan-derived nitrogen-doped carbon for efficient hydrogen evolution in a broad pH range. Issue 86 (10th October 2016) - Pu, Zonghua; Wang, Min; Kou, Zongkui; Amiinu, Ibrahim Saana; Mu, Shichun
Abstract : Mo2 C QDs/NGCLs exhibit high catalytic activity and durability for the hydrogen evolution reaction in a broad pH range. Abstract : A Mo2 C quantum dot (averagely 2 nm) embedded N-doped graphitic carbon layer (Mo2 C QD/NGCL) is prepared through a simple, green and scalable solid-state reaction. This material exhibits remarkable hydrogen evolution reaction (HER) catalytic activity and durability at all pH values owing to the synergistic effect between Mo2 C QDs and NGCLs.